Development of Patterns for Embroidered shirt Products from the Karen Community in Ban Huai Yuak, Si Satchanalai District, Sukhothai According to Thai Cultural Product Guidelines - Pantung, Pronchai; Soodsang, Nirat (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
This study has objectives as follows: 1) to develop Karen shirt products, Ban Huai Yuak, Si Satchanalai District, Sukhothai using Embroidery technique and 2) to evaluate the customer satisfaction toward the Karen Embroidery pattern in Ban Huai Yuak, Si Satchanalai District, Sukhothai. This study is done using interview and questionnaires to collect data. Samples are selected using the purposive sampling. Samples are 106 experts in Thai cultural products of the Karen community, Ban Huai Yuak, Si Satchanalai District, Sukhothai and customers in Sukhothai Historical Park. Data analysis is done using percentage, mean, and standard deviation. The results show that material and tools for producing hand-woven fabric products, Embroidery pattern, hand-woven fabric products, and the design of Karen shirt pattern are inspired by the nature such as starburst, sunflower, pink, melampodium, and Peregrina. The evaluation is done according to Thai Cultural Product Guidelines. The art component creativity and aesthetics have the score of very high ( = 5.00) and the commercial feasibility has the score of very high ( = 4.67). The customer satisfaction toward the Karen Embroidery pattern in Ban Huai Yuak in terms of usefulness has the score of high ( = 4.33), the shape has the score of high ( = 4.38) and the beauty has the score of high ( = 4.35).